Tryptophan was metabolized into beneficial metabolites against coronary heart disease or prevented from producing harmful metabolites by the in vitro drug screening model based on Clostridium sporogenes - Tian, XiaoXue; Wu, Yuanyuan; Duan, Cheng; Zhou, Xiaohong; Li, Yong; Zheng, Jiabin; Lai, Weihua; Zhang, Shuyao; Cao, Lixiang; Zhong, Shilong (Frontiers in Microbiology, 2022)
In our previous study of 2130 Chinese patients with coronary heart disease (CHD), we found that tryptophan (TRP) metabolites contributed to elevated risks of death. Many TRP-derived metabolites require the participation of intestinal bacteria to produce, and they play an important role in the pathogenesis of metabolic diseases such as CHD. So it is necessary to metabolize TRP into beneficial metabolites against CHD or prevent the production of harmful metabolites through external intervention. Indole-3-butyric acid (IBA) may be a key point of gut microbiota that causes TRP metabolism disorder and affects major adverse cardiovascular events in CHD. Therefore, this study aimed to develop a method based on in vitro culture bacteria to evaluate the effects of IBA on specific microbial metabolites quickly. We detected the concentrations of TRP and its metabolites in 11 bacterial strains isolated from feces using liquid chromatography–mass spectrometry, and selected Clostridium sporogenes as the model strain. Then, IBA was used in our model to explore its effect on TRP metabolism. Results demonstrated that the optimal culture conditions of C. sporogenes were as follows: initial pH, 6.8; culture temperature, 37 °C; and inoculum amount, 2%. Furthermore, we found that IBA significantly inhibited the production of indole-3-propionic acid and increased the levels of 5-hydroxyindole-3-acetic acid and TRP. This new bacteria-specific in vitro model provides a flexible, reproducible, and cost-effective tool for identifying harmful agents that can decrease the levels of beneficial TRP metabolites. It will be helpful for researchers when developing innovative strategies for studying gut microbiota.